Know the Map, Avoid Danger: Geographic Information System-Based Lembang Fault Disaster Mitigation Education at Langensari 2 Elementary School - Deni Sopiyan; Fitri Rizqiati; Haris Supriatna; Rinda Tiara; Naida Putri Asyaidah; Fitria Nurhayati; Intan Nurlatifah; Chandra Aprilians; Pahni Hanawan; Muhamad Aliph Fauzansyah; Muhamad Yafi; Muhamad Rivael Saputra (LPPM STMIK Mardira Indonesia, 2026)
The community service team, comprising academics and students from STMIK Mardira Indonesia, has initiated a project focused on disaster mitigation related to the Lembang Fault for elementary school pupils at State Elementary School 2 Langensari Lembang. The Lembang region and its vicinity are susceptible to seismic threats owing to the active geological characteristics of the Lembang Fault. A lack of comprehension within the community, particularly among school-age students, about disaster risks and mitigation may exacerbate vulnerability during a disaster. This community service initiative seeks to enhance students' understanding and awareness of the potential hazards posed by the Lembang Fault through disaster mitigation education using Geographic Information Systems (GIS). The implementation methods include interactive content delivery, the introduction of digital maps of disaster-prone regions, basic earthquake-mitigation simulations, and the assessment of student comprehension before and after the activities. The application of GIS facilitates the geographical visualization of the Lembang Fault, earthquake-prone areas, and the adjacent school environment, thereby enhancing student comprehension. This initiative seeks to foster a disaster-aware culture from a young age and help mitigate catastrophe risk in elementary school environments.